All‐Sky Interferometric Meteor Radar Observations of Zonal Structure and Drifts of Low‐Latitude Ionospheric E Region Irregularities. Issue 12 (13th December 2019) - Wang, Ye; Li, Guozhu; Ning, Baiqi; Yang, Sipeng; Sun, Wenjie; Yu, You
Abstract: All‐sky interferometric meteor radar has been operated worldwide for the measurements of neutral winds in the mesopause region. In this paper, we employ an all‐sky meteor radar and an ionospheric radar, which are situated at Ledong (18.4°N, 109°E) and Sanya (18.3°N, 109.6°E), respectively, and both have the interferometry capability, to study the zonal structure and drifts of ionospheric E region irregularities producing continuous and quasiperiodic echoes. We use the collocated optical meteor observations to calibrate the radar system phase offsets for interferometry measurements. A good correspondence between the irregularity measurements from both radars was found. The observations show that the quasiperiodic striations with both negative and positive slopes in radar range‐time‐intensity maps were produced by spatially separated irregularity structures, which drift through the radar field of view. The continuous echoes were due to irregularities generated locally. Specifically, comparing with ionospheric radar, all‐sky meteor radar has a much wider field of view that can provide E region irregularity information over a large zonal region of more than 300 km. It is suggested that all‐sky meteor radar provides a capability to probe ionospheric E region irregularities and to trace their movements. Plain Language Summary: The interferometry observations of ionospheric E region irregularities from a conventional all‐sky meteor radar and an ionospheric radar are reported. The results show the feasibility of making ionospheric E region irregularity measurements and tracing their movements over a large zonal field of view of more than 300 km with conventional meteor radars. Since there are tens of such meteor radars continuously operated at middle and low latitudes, the interferometry observations with these meteor radars would contribute to a better understanding of worldwide ionospheric E region irregularities. Key Points: Interferometry observations of ionospheric E region irregularities are made with an all‐sky meteor radar The zonal structure and movements of E region irregularities over a zonal field of view of more than 300 km are revealed by meteor radar Comparison of meteor radar E region irregularity observations with ionospheric radar shows a good correspondence